Comparison of PICU Cost and Severity-Adjusted Cost Between Patients With SIRS-Defined Sepsis and Those With Age-Adapted SOFA-Defined Sepsis - Zhang, Xuepeng; Sun, Kaibo; Lu, Guoyan; Feng, Liwei; Chen, Siyuan; Ji, Yi (Frontiers in Pediatrics, 2021)
Background: The 2005 International Pediatric Sepsis Consensus definition is considered to lack specificity and may lead to the admission of low-risk patients to the pediatric intensive care unit (PICU). The aim of this study was to compare the PICU cost and the severity-adjusted cost between patients with sepsis defined by the 2005 International Pediatric Sepsis Consensus and those diagnosed using the age-adapted Sepsis-3 criteria. Methods: Septic children identified by the 2005 Consensus were screened for enrollment. The enrolled children were stratified into two subgroups using the age-adapted Sepsis 3.0 definition. A comparison was made between the subgroups of sepsis 3.0-defined children and nonsepsis 3.0-defined septic children. The Severity Adjusted ICU Cost (SAIC) was used to evaluate the case-mixed severity-adjusted costs of the study population. Coefficients in linear regression analyses in subgroups were calculated for presenting variation of PICU costs for every unit change of PRISM score. Results: A total of 399 children were enrolled. The PICU length of stay was longer in the sepsis 3.0 group than in the nonsepsis 3.0 group (median [IQR], 9.0 [5.0, 15.0] vs 6.0 [3.0, 9.0]; P < 0.001). Pediatric risk of mortality (PRISM) scores and mortality were significantly higher in sepsis 3.0-defined septic patients. The total costs and daily costs in the PICU were both significantly lower in the nonsepsis 3.0 group (P < 0.001). The severity-adjusted ICU cost in the nonsepsis 3.0 group was lower than that in the sepsis 3.0 group (median [IQR], 7125 [3588, 11134] vs 9364 [5680, 15876]; P = 0.001). There was no significant difference among the regression coefficients. Conclusions: The 2005 International Pediatric Sepsis Consensus definition does not lead to more PICU costs after considering illness severity.